Granulocyte colony-stimulating factor in patients with acute ischemic stroke: results of the AX200 for ischemic stroke trial - Ringelstein, Erich B.; Thijs, Vincent; Norrving, Bo; Chamorro, Angel; Aichner, Franz; Grond, Martin; Saver, Jeff; Laage, Rico; Schneider, Armin; Rathgeb, Frank; Vogt, Gerhard; Charissé, Gabriele; et al. (Stroke, 2013)
Background and Purpose — Granulocyte colony-stimulating factor (G-CSF; AX200; Filgrastim) is a stroke drug candidate with excellent preclinical evidence for efficacy. A previous phase IIa dose-escalation study suggested potential efficacy in humans. The present large phase IIb trial was powered to detect clinical efficacy in acute ischemic stroke patients. Methods— G-CSF (135 µg/kg body weight intravenous over 72 hours) was tested against placebo in 328 patients in a multinational, multicenter, randomized, and placebo-controlled trial (NCT00927836; www.clinicaltrial.gov). Main inclusion criteria were ≤9-hour time window after stroke onset, infarct localization in the middle cerebral artery territory, baseline National Institutes of Health Stroke Scale score range of 6 to 22, and baseline diffusion-weighted imaging lesion size ≥15 mL. Primary and secondary end points were the modified Rankin scale score and the National Institutes of Health Stroke Scale score at day 90, respectively. Data were analyzed using a prespecified model that adjusted for age, National Institutes of Health Stroke Scale score at baseline, and initial infarct volume (diffusion-weighted imaging). Results— G-CSF treatment failed to meet the primary and secondary end points of the trial. For additional end points such as mortality, Barthel index, or infarct size at day 30, G-CSF did not show efficacy either. There was, however, a trend for reduced infarct growth in the G-CSF group. G-CSF showed the expected peripheral pharmacokinetic and pharmacodynamic profiles, with a strong increase in leukocytes and monocytes. In parallel, the cytokine profile showed a significant decrease of interleukin-1. Conclusions— G-CSF, a novel and promising drug candidate with a comprehensive preclinical and clinical package, did not provide any significant benefit with respect to either clinical outcome or imaging biomarkers. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT00927836.
Gesehen am 13.01.2022